Efektivitas Promosi Kesehatan Menggunakan Audiovisual terhadap Pendidikan Seks Untuk Anak Prasekolah di TK Aisyiyah Kota Bukittinggi - Mariyona, Kartika; Rusdi, Pagdya Haninda Nusantri; Nugrahmi, Mega Ade (Universitas Batanghari Jambi, 2025)
The purpose of this study was to determine the effectiveness of health promotion using audiovisuals on sex education for preschool children at Aisyiyah Kindergarten in Bukittinggi City. This study used a quasi-experimental method with a pre-test and post-test design without a control group, and applied a simple random sampling technique. Respondents were 10 Aisyiyah Kindergarten students in Bukittinggi City. Research data analysis used the Wilcoxon test. The results of this study prove that there is an increase in understanding of sex education for preschool children at Aisyiyah Kindergarten in Bukittinggi City by using audiovisuals.